Genetic diversity in the anabantids Sandelia capensis and S. bainsii: A phylogeographic and phylogenetic investigation - Bloomer, Paulette (University of Pretoria, 2013)
Dissertation (MSc (Genetics))--University of Pretoria, 2006.